Short- and long-term outcomes of laparoscopic low anterior resection with “dog ear” invagination anastomosis for mid and distal rectal cancer a propensity score matched analysis - Zhang, L.; Xie, Z.; Gong, L.; Lv, X. (Frontiers in Surgery, 2023)
Background: The lateral intersecting margin (dog-ear) was a weak spot of the double stapled technique (DST), We designed "dog-ear" invagination anastomosis (DAIA), which could eliminate the "dog-ear" in laparoscopic anterior resection. Patients and methods: A total of 202 patients underwent elective curative LLAR+DST (n =143) or LLAR+DAIA (n = 59) were enrolled in the study. Propensity score matching (PSM) was used to minimize the adverse effects. The clinical data between LLAR+DST and LLAR+DAIA was compared, and the effect of factors on overall survival (OS) and disease-free survival (DFS) was analyzed. Results: After PSM, 53 pairs of the LLRA+DST and LLRA+DAIA patients were enrolled in the study. The LLRA+DAIA group has a higher level (3.50 ±1.03 vs. 2.87 ±1.10, p=0.01) of the anastomosis than that of the LLRA+DST group. Patients in LLAR+DAIA group have a lower incidence of protecting loop ileostomy compared to LLAR+DST group(20.75% vs. 5.66%, P<0.05). The LLRA+DAIA patients presented better rates of LARS compare to LLRA+DST patients at 6 months (major LARS 37.74%(n=20) vs. 67.93% (n = 36); p = 0.007) and 12months (major LARS 13.21% (n = 7) vs. 20.37% (n = 11); p = 0.03) after surgery. The OS and DFS rates were similar (P > 0.05). Conclusion: Laparoscopic low anterior resection with "dog-ear" invagination anastomosis technique are well-established procedures for patients with low rectal cancer. "Dog-ear" invagination anastomosis technique may reduce the incidence of protecting loop ileostomy and significantly affect LARS score, and demonstrate a positive impact on the quality of life after surgery.